Translation invariance in the responses to faces of single neurons in the temporal visual cortical areas of the alert macaque. - Tovee, M; Rolls, E; Azzopardi, P (1994)
1. The responses of single neurons in the inferior temporal cortex and the cortex in the banks of the anterior part of the superior temporal sulcus of three awake, behaving macaques were recorded during a visual fixation task. Stimulus images subtending 17 or 8.5 degrees were presented in the center of the display area, and fixation was either at the center of the display area, or at one of four positions that were on the stimulus, or several degrees off the edge of the test stimulus. The experiments were performed with face-selective cells, and the responses were compared for fixation at each position for both effective and noneffective face stimuli for each cell. 2. The firing rates of most neurons to an effective image did not significantly alter when visual fixation was as far eccentric as the edge of the face, and they showed only a small reduction when the fixation point was up to 4 degrees from the edge of the face. Moreover, stimulus selectivity across faces was maintained throughout this region of the visual field. 3. The centers of the receptive fields of the cells, as shown by the calculated "centers of gravity," were close to the fovea, with almost all being within 3 degrees of the fovea. 4. The receptive fields of the cells typically crossed the vertical midline for at least 5 degrees. 5. Information theory procedures were used to analyze the spike trains of the visual neurons. Nearly six times more information was carried by these neurons' firing rate about the identity of an image than about its position in the visual field. Thus the information theory analysis showed that the responses of these neurons reflected information about which stimulus had been seen in a relatively translation invariant way. 6. Principal component analysis showed that principal component 1 (PC1) is related primarily to firing rate and reflected information primarily about stimulus identity. (For identity PC2 added only 14% more information to that contained in PC1.) Principal component 2 (PC2) was more closely related to neuronal response latencies, which increased with increasing eccentricity of the image in the visual field. PC2 reflected information about the position of the stimulus in the visual field, in that PC2 added 109% more information to that contained in PC1 about the position of the stimulus in the visual field.(ABSTRACT TRUNCATED AT 400 WORDS)